2005
DOI: 10.1128/jb.187.22.7716-7726.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Acquisition ofLegionellaType IV Secretion Substrates via Interdomain Horizontal Gene Transfer

Abstract: Intracellular pathogens exploit host cell functions to create a replication niche inside eukaryotic cells. The causative agent of Legionnaires' disease, the ␥-proteobacterium Legionella pneumophila, resides and replicates within a modified vacuole of protozoan and mammalian cells. L. pneumophila translocates effector proteins into host cells through the Icm-Dot complex, a specialized type IVB secretion system that is required for intracellular growth. To find out if some effector proteins may have been acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
318
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(329 citation statements)
references
References 60 publications
8
318
0
3
Order By: Relevance
“…Interestingly, many of these potential virulence factors never had been identified in a prokaryotic genome before the discovery in L. pneumophila, suggesting that L. pneumophila may have developed specific mechanisms to cross talk with its eukaryotic hosts (Bruggemann et al 2006). The presence of a high number of eukaryoticlike proteins in the genus Legionella was further confirmed when analyzing different L. pneumophila and L. longbeachae genomes (de Felipe et al 2005;Cazalet et al 2010;Kozak et al 2010;Schroeder et al 2010;Gomez-Valero et al 2011b). Thus, the Legionella genomes reflect the interaction of this bacterium with amoeba, which is probably the driving force in the evolution of Legionella pathogenicity.…”
Section: The Mobilome Of Legionella Has a Diverse Originmentioning
confidence: 64%
See 2 more Smart Citations
“…Interestingly, many of these potential virulence factors never had been identified in a prokaryotic genome before the discovery in L. pneumophila, suggesting that L. pneumophila may have developed specific mechanisms to cross talk with its eukaryotic hosts (Bruggemann et al 2006). The presence of a high number of eukaryoticlike proteins in the genus Legionella was further confirmed when analyzing different L. pneumophila and L. longbeachae genomes (de Felipe et al 2005;Cazalet et al 2010;Kozak et al 2010;Schroeder et al 2010;Gomez-Valero et al 2011b). Thus, the Legionella genomes reflect the interaction of this bacterium with amoeba, which is probably the driving force in the evolution of Legionella pathogenicity.…”
Section: The Mobilome Of Legionella Has a Diverse Originmentioning
confidence: 64%
“…Gomez-Valero and C. Buchrieser since then. In 2004, more than 60 of these proteins were described in the genomes of strains Paris and Lens (Cazalet et al 2004) and in 2005, in strain Philadelphia (de Felipe et al 2005). Later, the analysis of the distribution of these genes among more than 200 L. pneumophila strains using DNA arrays showed that the conservation of certain eukaryotic-like genes within the species L. pneumophila was high, indicating strong environmental selection pressures for their preservation (Cazalet et al 2008).…”
Section: The Mobilome Of Legionella Has a Diverse Originmentioning
confidence: 99%
See 1 more Smart Citation
“…The L. pneumophila Icm/Dot type IV secretion system is composed of about 23 complex components, three accessory proteins, and a large number of IDTS (for reviews, see references 42 and 49), and many additional proteins have been suggested to be putative IDTS (6,12,29,61). This very large number of components must be coordinated at the level of gene expression in order to result in a successful infection and intracellular multiplication.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that horizontal gene transfer from eukaryotes was a major mechanism in this co-evolution. 5 Two types of SVFs are currently in the spotlight ( Fig. 2): accessory factors of Rab GTPases and ankyrin repeat-containing proteins, Anks.…”
Section: The Process Of Cell Takeovermentioning
confidence: 99%